Pore-scale modelling of particle migration in loose sandstone - Zheng, Wei; Tang, Chenyang; Cai, Shaobin; He, Yufei; Jiang, Junzhe; Li, Ke; Zhang, Zhaonian; Chen, Lifeng (Frontiers in Earth Science, 2024)
During the development of loose sandstone reservoirs, the issue of production decline and bottomhole pressure reduction caused by particle migration is widespread, directly impacting well productivity. Understanding the mechanism of particle migration in sandstone and determining the main factors affecting this process are crucial for improving oilfield development. This study focuses on an offshore oilfield and utilizes real digital core models constructed through CT scanning technology. Numerical simulations of fluid-solid coupling were conducted using Fluent and EDEM software to establish a coupled particle-oil-water flow model. This model was employed to investigate particle blockage modes and the effects of particle size, concentration, and injection rate on particle migration in the reservoir. The results indicate that particle migration primarily occurs in two blockage modes: pinhole blockage and bridging blockage. In sandstone, particle retention rates are primarily controlled by particle size, with larger pore-to-particle size ratios leading to higher retention rates. Particle concentration and injection rate have relatively minor effects on the final retention rate. As for migration distance, particle size significantly influences migration, with larger pore-to-particle size ratios resulting in shorter migration distances. Under low concentration conditions, concentration has a minimal effect on migration distance. However, as the injection rate increases, migration distance also increases. In summary, this study clarifies the particle migration mechanisms and the key factors controlling migration in sandstone formations, providing valuable theoretical support for oilfield development.